Development, evaluation and release of Guarani, an early maturity upland rice cultivar - Guimarães, Elcio Perpétuo; Morais, Orlando Peixoto de; Barros, Luiz Gonzaga de; Neiva, Luiz Carlos da S.; Soares, Antonio Alves; Bazoni, Reinaldo; Prabhu, Anne Sitarama; Pinheiro, Beatriz da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
The process of selection of the line CNAx 095-BM 30-BM 9-28 was described and the results of the evaluations presented. The line originated from the cross 63-83/IAC 25 after two cycles of modified bulk (F2 and F3) followed by one cycle of pedigree selection (F4). Grain yield, leaf and neck blast were evaluated in preliminary and advanced yield trials conducted in four Brazilian states. The line overall grain yield mean was 19.4% higher than that of the check (IAC 165). For the states of Mato Grosso, Goiás, Minas Gerais and Mato Grosso do Sul the grain yield increase over the check was 17.7%, 22.7%, 26.6% and 7.3%, respectively. The line showed higher leaf and neck blast resistance. The line was agronomically described and commercialy released with the name of Guarani.